Produtividade do feijoeiro (Phaseolus vulgaris) cultivado sob efeito residual da adubação do milho de segunda safra - Simione, Júlia Rodrigues (Universidade Federal de São Carlos, 2017)
One of the great challenges for the bean crop is to increase productivity and, at the same time, improve fertilization management using new technologies. The objective of this work was to evaluate the effect of residual fertilization of the winter corn crop on the productivity and biometric parameters of the common bean crop (IPR Campos Gerais cultivar), sown in succession. The experiment was conducted in the experimental area at the UFSCar - Center for Agricultural Sciences. The treatments were arranged in a 2x3+1 factorial scheme, with four replications, with the source factor of primary macronutrients at two levels, conventional mineral (M – added in the form of simple fertilizers, in proportion equivalent to 05-17-10) and organomineral (OM - Farture® 05-17-10), the dose factor in three levels, and the control without the addition of fertilizers: T1 - control (0 kg ha-1); T2 - 200 kg ha-1 of OM (equivalent to ½ DR); T3 - 400 kg ha-1 of OM (recommended dose - DR); T4 - 600 kg ha-1 of OM (equivalent to 1½ DR); T5 - 200 kg ha-1 of M; T6 - 400 kg ha-1 of M; T7 - 600 kg ha-1 of M. At 80 days after emergence of the bean plants, the following parameters were evaluated: phytomass (kg), number of grains per pod, pod length (cm), number of pods per plant, mass of 100 seeds (g), and production (g 10 plants-1). At the flowering stage (R1, 44 days after plant emergence), plant tissue was collected for analysis of foliar macronutrient contents. The results were submitted to analysis of variance and, when significant by the F test (p<0.05), they were evaluated by the Scott-Knot test (p<0.05). The types and different doses of fertilization, used in the winter corn crop, did not interfere on the biometric parameters and production of the bean plant. The leaf contents of P, K, Mg, and S were lower than those considered adequate for the bean crop. However, it was concluded that the residual effect of corn fertilization, regardless of type and dose, ensured high bean yields, which ranged from 3,200 to 4,315 kg ha-1.
Yield of common bean (Phaseolus vulgaris) cultivated under residual effect of winter corn crop fertilization
Keywords: Adubação organomineral; Common bean crop; IPR Campos Gerais; Feijoeiro-comum; Fertilization management; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO